From stereotype to reality: A pilot study on the use of science, technology, engineering, and mathematics and STEAM in design education in Taiwan - Sun, Yikang; Ni, Chien-Chih; Lin, Rungtai (Frontiers in Education, 2023)
Currently, STEAM interventions in design education are a relatively new phenomenon. A design education system derives from three major ideas from the Bauhaus: 1) art and technology: a new unity; 2) human-centered design; and 3) interdisciplinarity, which is the essence and connotation of STEAM. In the transition from STEM to STEAM, the concept and mindset of art connect the four disciplines within STEM, elevating these tools and methods into a strategy. It is urgently necessary for design educators to restructure their curriculum using STEAM models and thought. However, there is no evidence that the integration of these disciplines will improve design education for the public. Consequently, this study examines the perception of educators and the public regarding the use of STEAM in design education. Using expert interviews, six design schools were selected as samples, and questionnaires were used to collect and analyze the views of different groups of people. According to the results, the expert group scored fairly high; and other groups will form stereotypes based on the characteristics of the school, resulting in a polarized assessment of STEAM. All groups displayed cognitive differences in many aspects. According to this study, the STEAM model needs to be incorporated into design education, but it is necessary to determine objectively the relationship between the five attributes and their relative importance within different design disciplines. Under the premise of complying with policies, regulations, and the actual situation of the school, the design of the curriculum planning needs to be adjusted and supplemented in a timely manner according to the STEAM model. Specifically, it cannot be arranged arbitrarily for STEAM, but it should also let students understand what STEAM is about so that they can understand why these courses exist. Furthermore, researchers should examine the effectiveness of these courses over time by conducting a phased retrospective.